2022
DOI: 10.1177/13634607221077554
|View full text |Cite
|
Sign up to set email alerts
|

Sex as self-injury: The appearance of a new diagnostic category in Sweden

Abstract: “Sex as self-injury” is a well-established concept within Swedish society and is a new label for categorizing sexual risk-taking. The phenomenon has been discussed in Sweden since 2008, and about a decade later the concept appeared for the first time in Swedish scientific literature. “Sex as self-injury” is not yet an idea accepted by the international research field, but it can be assumed that it will eventually reach the international arena: the discourse about “self-destructive sex” has the potential to be … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…It is also possible that certain risky sexual behaviors, such as condomless casual sex, could be acts of self-harm. Studies in Taiwan and Sweden have indicated that risky sexual behaviors can be self-destructive acts [52,53]. Nonetheless, further studies are necessary to ascertain such hypotheses.…”
Section: Discussionmentioning
confidence: 99%
“…It is also possible that certain risky sexual behaviors, such as condomless casual sex, could be acts of self-harm. Studies in Taiwan and Sweden have indicated that risky sexual behaviors can be self-destructive acts [52,53]. Nonetheless, further studies are necessary to ascertain such hypotheses.…”
Section: Discussionmentioning
confidence: 99%
“…Females who engage in sexual risky behaviours are more likely to experience forced sex [18], and be physically assaulted and sexually victimized by their intimate partners [19]. In addition, sexual risky behaviours were found to be positively correlated with several negative mental health consequences, including poor self-rated mental health, high depression and high anxiety [20,21], and were regarded by some researchers as self-destructive acts [22,23]. Due to their detrimental outcomes, practicing risky sex constitute a major cause of burden of disease [3], and a signi cant and growing public health concern that is likely to continue to be challenging in future [24].…”
Section: Introductionmentioning
confidence: 99%